A comprehensive analysis of two types of xenogeneic bone particles for use in maxillofacial bone regeneration therapies - Olimpia Ortiz-Arrabal; Mario Anibal Rodriguez; Jesús Chato-Astrain; Miguel Ángel Martín-Piedra; Ingrid Garzón; Víctor Carriel; Ricardo Fernández-Valadés; Antonio España-López; Miguel Alaminos; Ismael Angel Rodriguez (PLoS ONE, 2025)
Regeneration of maxillofacial bone structures is challenging. One strategy for bone damage repair involves using bone filler particles. This study analyzed the regenerative potential of deproteinized bone particles (DP) and collagen-based bone particles (CP) to determine the effectiveness of each biomaterial in bone repair. Structural analysis using scanning electron microscopy and 3D scanning showed that DP and CP were structurally similar, comprising a heterogeneous mixture of bone particles of varying sizes and shapes. Ex vivo analyses, including morphological evaluation, LIVE & DEAD assays, and DNA quantification, demonstrated high biocompatibility of CP and DP with human cells in both direct and indirect contact at 24, 48, and 72 hours. Both particles were grafted onto Wistar rats with a critical mandibular defect for two months. Computed tomography revealed significant defect reduction in the CP group, but not in the DP group, compared to negative controls without any bone particles. Histological analysis showed biocompatibility of both particles in vivo and identified regenerative tissue with collagen fibers and mineralized spots in CP and DP, with more mineralized spots in DP. Histochemistry and immunohistochemistry confirmed collagen, proteoglycans, and osteocalcin presence in the regeneration area of CP and DP. These results confirm the biocompatibility and potential of both particle types for maxillofacial bone regeneration, particularly CP. Future studies should assess their clinical usefulness for patients with cleft palate, mandibular damage, and other maxillofacial applications involving tissue engineering techniques.